Small doses of epinephrine prolong the recovery from a rocuronium-induced neuromuscular block: a case report - Schmitt, Hubert (BMC Anesthesiology, 2018)
BACKGROUND: During anaesthesia it is not uncommon to administer epinephrine in patients blocked by non-depolarizing muscle relaxants. However, there are few reports on possible interaction of epinephrine with neuromuscular transmission in humans. CASE PRESENTATION: An otherwise healthy 74-yr-old man underwent transurethral resection of a benign prostatic hyperplasia under total intravenous anaesthesia. Because of repeated drop in heart rate and blood pressure the patient received in total three bolus of epinephrine 5 μg, respectively. Each time this small dose of epinephrine intensified a rocuronium-induced neuromuscular block verified by acceleromygraphy. Further anaesthetic course was uneventful. CONCLUSIONS: In this case reported here small doses of intravenously administered epinephrine markedly prolonged a rocuronium-induced neuromuscular block. Given the widely used co-administration of epinephrine and muscle relaxants possible adrenergic interference with neuromuscular transmission would have implications for daily anaesthetic practice.
EVALuna2:212909